Investigating the effect of social support, social capital, and coping on the positive state of mind of Iranian older people with human immunodeficiency virus/acquired immunodeficiency syndrome - Neda SoleimanvandiAzar; Nasibeh Zanjari; Salah Eddin Karimi; Seyed Fahim Irandoost; Mohammad Ali Mohammadi Gharehghani; Arash Ziapour; Sina Ahmadi; Mozhgan Moshtagh (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Social resources help to adapt to stress and might positively affect the well-being of individuals with severe conditions like human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). The present study investigates the effect of social support, social capital, and coping in a positive state of mind of Iranian older people with HIV/AIDS. MATERIALS AND METHODS: This cross-sectional study was conducted on 160 older people with HIV referred to AIDS clinics in Tehran in 2019. Samples were randomly selected from patients aged 50 years and older. Data were collected using a questionnaire, a positive state of mind, social capital, coping, social support, and a checklist of demographical variables. Data analysis was performed using SPSS software version 21. RESULTS: A significant positive correlation was found between social support, social capital, coping, education, and a positive state of mind. A significant negative correlation was also found between age, several chronic diseases of the patient, and a positive state of mind. The linear regression results showed that social support, social capital, coping, and education improved the positive state of mind. CONCLUSIONS: Based on our findings, we believe that social and psychological interventions effectively enhance patients' positive state of mind with HIV and ultimately, improve their quality of life.